Evaluation the performance characteristics in platform diving - Nomura, T.; Goya, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
It was aimed to evaluate the characteristics of the platform diving performance. Twelve of the men`s 10m platform-diving finalists in the Japan Championship 2017 were analyzed. Digital movies taken from the diagonal side upper part of the stands were used. Two-dimensional DLT analysis software (Note-Player 2) which customized for the diving motion analysis, applied the two-point perspective method. The greater trochanter point was digitized from take-off to entering the pool in the 10m platform diving performance. The parabolic motion elements were determined by least-squares approximation of the actual value as the time function equation 1. Parabola_x (t) = a * t, Parabola_y(t) = b * t+0.5 * g * t2 (Equation 1) Here, x = the horizontal component, y = the vertical component, t = the elapsed time since take-off, a = the projecting horizontal velocity, b= the projecting vertical velocity, and g = the gravitational acceleration of -9.80655 m(s2. The rotational motion elements were determined by least-squares approximation of the parabolic residuals as the time function equation 2. Rotation_x(t) = c * cos(2*pi * d * t+e)+f, Rotation_y(t) = c * sin(2*pi * d * t+e)+h (Equation 2) Here, x = the horizontal component, y = the vertical component, t = the elapsed time since take-off, pi = the circumference ratio, c = the amplitude, d = the frequency, e = the wave phase, f = the horizontal shift of the center of the rotation, and h = the vertical shift of the center of the rotation. The correlation coefficient between parabolic motion elements and position coordinates were significant (0.85 to 0.99, p< 0.01). During the rotational period, the residual of the parabolic motion element had a high correlation with the rotational motion element. However, there was a tendency to diverge during the twisting and/or the final half rotation where the rotation posture changed. Horizontal distance (0.21 ± 0.21 m) from hand-entering point to foot entering point in water was strongly related to the diving score / the difficulty level (19.87 ± 3.28 point, r = - 0.83, p< 0.01). The vertical shift of the center of rotation (-0.02 ± 0.07 m) from the parabolic motion element increased with the number of rotations (3.12 ± 0.60 cycles, r = 0.76, p < 0.01).